Effect of markets temperature on stock-price: Monte Carlo simulation on spin model - Arjaree Thongon (2018)
In this study, we used the Monte Carlo simulations to investigate the phenomena in the stock-price market which we considered as a function of temperature and external field which reflect the effects of the environment (e.g., access to external information). The Monte Carlo simulation was used to simulate the Ising model with heat-bath algorithm. The results show that the average orientation of the agents varies with the external field at constant temperature. In other words, the agents always buy when they get good news. And at high temperature, with constant positive external field, the average orientation of the agents is decreased to near zero. © Springer International Publishing Switzerland 2014.